2005
DOI: 10.1260/0263092054531000
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance of Low Frequency Tones and Objective Evaluation Methods

Abstract: Annoyance of low frequency pure and combined tones was measured in a laboratory experiment. Three low frequency tones at frequencies of 31.5, 50 and 80 Hz at four sound pressure levels, from about 6 dB to 24 dB above average hearing threshold, were selected as pure tones. The combined tones were combinations of two tones: the four levels of 31.5, 50 and 80 Hz tones and a constant level 40 Hz tone. The results showed that the rate of increase in annoyance of pure tones with increase in the sound pressure level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Recently, Subedi et al, [40] measured annoyance of low frequency pure and combined tones in a laboratory experiment. They compared these results (median values) with the evaluation obtained from three objective methods, namely a method based on Moore's loudness model, the total energy summation model (in this study referred to as the total SPL), and the low frequency A-weighting.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Subedi et al, [40] measured annoyance of low frequency pure and combined tones in a laboratory experiment. They compared these results (median values) with the evaluation obtained from three objective methods, namely a method based on Moore's loudness model, the total energy summation model (in this study referred to as the total SPL), and the low frequency A-weighting.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Subedi et al 36 measured annoyance of low frequency pure and combined tones in a laboratory experiment. They compared these results (median values) with the evaluation obtained from objective methods based on Moore's loudness model, the total energy summation (in this study referred to as the total sound pressure level) and the low frequency A-weighting, and found that the latter one yielded the best correlation.…”
Section: Discussionmentioning
confidence: 99%
“…At low and particularly infrasonic frequencies, the loudness increases more steeply above the hearing threshold than at higher frequencies, [2][3][4][5] and a sound moderately above threshold may be perceived not only loud but also annoying. [6][7][8][9] Since there is a natural spread in hearing thresholds, a sound that is inaudible or soft to some people may be loud and annoying to others. Low-frequency noise above the hearing threshold may also affect task performance 10 and cause sleep disturbances.…”
Section: A Low-frequency Sound and Infrasoundmentioning
confidence: 99%